Uji Efikasi Berbagai Media Agens Antagonis Paenibacillus polymyxa Terhadap Penyakit Bacterial Leaf Blight Pada Tanaman Padi (Oryza sativa) - Yogaswara, Muhammad Agung; Sondari, Nunung; Ulfah, Indriana (Fakultas Pertanian Universitas Winaya Mukti, 2023)
An experiment was carried out in Margasari Village, Dawuan District, Subang Regency, from July 2020 to November 2020. The purpose of this study was to study the efficacy of various media of the antagonist agent Paenibacillus polymyxa in controlling Bacterial Leaf Blight in rice plants and to find the most effective and efficient media. to control Bacterial Leaf Blight in rice plants. The method used in this study was an experiment through field experiments, with a simple randomized block design consisting of six treatments and four replications. The experimental treatments consisted of: A (Sugar Potato Extract), B (Sweet Potato Extract), C (Sugar Cassava Extract), D (Soybean Extract), E (Sugar Rice Wash Water) and F (Control). The experimental results show that: (1) All the Paenibacillus polymyxa antagonist agent media in this experiment were effective in suppressing the intensity of the attack of Bacterial Leaf Blight (2) The more effective Paenibacillus polymyxa antagonist agent medium was treatment A (Sugar Potato Extract) which was able to suppress the intensity. attack was lower than the other treatments, so it had the most number of productive tillers and produced the highest average productivity of 8.08 tons ha-1.